A look at the free-viewing paradigm in eye-tracking research to assess positive attentional bias - Suslow, Thomas; Hoepfel, Dennis; Wenk, Taavi; Kersting, Anette; Günther, Vivien (Frontiers in Psychiatry, 2025)
Attention orientation toward positive stimuli may have mood-protective or mood-enhancing effects. Eye-tracking is an increasingly administered method to assess biased attention allocation and maintenance. In the present paper, we point to an underestimated but reliable method of eye-tracking research for measuring positive attentional bias and its temporal dynamics: the free-viewing paradigm. To date, few free-viewing eye-tracking studies have specifically examined positive attentional biases in healthy individuals. Against this background, we summarize findings from clinical and subclinical eye-tracking research using free viewing in healthy control groups. We discuss the observed time courses of positive attentional biases during experimental trials, which vary depending on type and number of presented stimuli, and make recommendations on which experimental conditions appear to be favorable for capturing dynamic time courses of positive attentional biases. We identify various individual difference factors that may influence the magnitude of positive attentional biases and should be considered in future studies. Time course analyses of eye-tracking data offer the opportunity to learn more about the time of onset and extent of increase in attention to positive information during free viewing and their relationships to individual difference variables. Directions for future research on positive attentional biases are discussed.